Heterogeneous trends of premature mortalities in Japan: joinpoint regression analysis of years of life lost from 2011 to 2019 - Satoshi Tsuboi; Tomosa Mine; Tetsuhito Fukushima (Elsevier, 2022)
Purpose: To assess long-term premature mortalities in Japan for providing evidence of strategies for sustainable development in population health. Methods: Descriptive study for observing the trends of premature mortalities due to 10 major causes and all-cause in Japan was conducted using governmental statistics taken between 2011 and 2019. Years of life lost (YLL) was calculated for each cause, and the trends of these were examined by joinpoint regression analysis. Results: The means of YLL for all-cause through 2011 to 2019 were 8,121,565.1 in males and 6,743,198.4 in females. For each cause, the trends of age-standardized YLL were downward except for malignant neoplasm of pancreas and heart failure in males, and malignant neoplasm of pancreas, malignant neoplasm of breast, and age-related physical debility in females. One significant joinpoint for heart failure was found in males, and one significant joinpoint for each of malignant neoplasm of pancreas and age-related physical debility were found in females. Conclusions: Premature mortalities due to malignant neoplasm of pancreas in both sexes, heart failure in males and malignant neoplasm of breast in females were issues to be prioritized for promoting population health in Japan.